Fe, Ni-modified ZIF-8 as a tensive precursor to derive N-doped carbon as Na and Li-ion batteries anodes. (19th February 2023) - Jia, Hongna; Wang, Yao; Zhao, Shuya; Wang, Haipeng; Ju, Na; Zhang, Xinyue; Li, Hong; Sun, Zejun; Sun, Hong-bin
Abstract: Carbon materials derived from metal-organic frameworks have attracted increasing attention as anodes for energy storage. In this study, Fe, Ni-doped ZIF-8 is carbonized at high temperature to obtain bimetallic Fe and Ni modified tension -relaxed carbon (FeNi@trC). Fe and Ni have opposite structural modification effects when the metal ions are doped into the ZIF-8 dodecahedron. The obtained carbon material maintains the regular dodecahedron morphology, which means the relaxation of tension and strong thermal stability during annealing. Moreover, the presence of nickel enhances the carbonization degree and electrochemical stability of FeNi@trC, while the calcination of the tensive ZIF-8 precursor offers more defect sites. The discharge capacities of FeNi@trC materials are stable at 182.9 mAh·g −1 and 567.9 mAh·g −1 for sodium-ion batterie (SIB) and lithium-ion batterie (LIB) at 0.05 A·g −1 . Compared with the current density of 0.05 A·g −1, the discharge capacity of SIB and LIB attenuates by 29.4% and 55.9% at 1 A·g −1, respectively, and the FeNi@trC shows good performance stability in the following cycles.